A Review: Improving Conceptual Understanding of Prospective Teacher Students Through an Interactive Web-Based STEM-PjBL Physics Material Model - Aris Doyan; Susilawati; Ahmad Harjono; Holis Angga Saputra (Jurnal Penelitian Pendidikan IPA, 2026)
This literature review examines the development of an interactive, web-based instructional model integrating Science, Technology, Engineering, and Mathematics with Project-Based Learning (STEM-PjBL) for physics material, aimed at improving the conceptual understanding of prospective (pre-service) teacher students. Following the PRISMA 2020 protocol, 336 records were identified from Scopus- and SINTA-indexed databases and other sources; after removing duplicates and screening for relevance, 20 primary studies published between 2018 and 2025 were included in the qualitative synthesis. The review finds that web-based STEM-PjBL models consistently improve conceptual understanding, critical thinking, and problem-solving skills, with reported effect sizes ranging from moderate to high (Cohen's d = 0.72–1.85; N-gain 0.30–0.59). Interactivity, authentic project design, and technology-enhanced pedagogical content knowledge (TPACK) emerge as the strongest predictors of learning gains among prospective teachers. Gaps remain in longitudinal evaluation, adaptive/AI-supported personalization, and standardized instruments for measuring conceptual change. The review proposes a conceptual web-based STEM-PjBL physics model and recommends directions for future research and development.